PENERAPAN SISTEM INFORMASI AKUNTANSI DENGAN MEDEXC DALAM MENGHASILAKAN LAPORAN KEUANGAN PADA UMKM : KILLISA DESAIN - Kurnia Riesty Utami (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to apply the preparation of financial reports using computerization in Killisa Design SMEs in the face of increasingly advanced developments in producing effective and efficient financial reports, of course in accordance with the standards expected by capital providers. The research method used in this research is descriptive qualitative method approach. By using the application of computerization, namely Microsoft Excel, it is one of the new breakthroughs to provide solutions to the problems MSMEs are currently facing. It is very important to separate the assets of each business because with this separation, business actors can find out how the continuity of their business is sign or just stagnant. Furthermore, the application of the use of computers to the preparation of financial reports needs to be carried out in other MSMEs in Banyuwangi Regency. Because the use of computerization makes it easier to make effective and efficient financial arrangements.